The contribution of Prof. Maja Razbojnikova-Frateva to the study of German-language literature and to German Studies in Bulgaria - Endreva, Maria (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2023)
The paper presents the contribution of Prof. Maja Razbojnikova-Frateva to the study of German-language literature.